1993
DOI: 10.1093/bja/71.6.835
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture in Anaesthesia for Hysterectomy

Abstract: We have studied the effects of electroacupuncture at classical acupuncture points, applied before and during surgery in patients undergoing hysterectomy, on postoperative pain and metabolic stress responses in a prospective, randomized and patient-blinded manner. Fifty otherwise healthy women were allocated randomly to receive or not receive electroacupuncture. Electroacupuncture was begun 20 min before skin incision and continued to the end of surgery. All patients received similar general anaesthesia and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 12 publications
0
20
0
8
Order By: Relevance
“…To our knowledge five prospective, controlled studies on acupuncture for postoperative pain relief are reported in such detail that reproduction would be possible (1)(2)(3)(4)(5). An analgesic effect of acupuncture was found in three of these studies (1, 2, 5) but not in the other two (3,4).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To our knowledge five prospective, controlled studies on acupuncture for postoperative pain relief are reported in such detail that reproduction would be possible (1)(2)(3)(4)(5). An analgesic effect of acupuncture was found in three of these studies (1, 2, 5) but not in the other two (3,4).…”
Section: Discussionmentioning
confidence: 94%
“…# Acta Anaesthesiologica Scandinavica 47 (2003) R EPORTS have differed as to the clinical value of acupuncture, since the method was introduced as an anaesthetic technique in China in 1958 (1)(2)(3)(4)(5). One factor contributing to difficulties associated with clinical studies on acupuncture is the technical problem regarding blinding (6).…”
Section: Accepted For Publication 20 March 2003mentioning
confidence: 99%
“…Bu etkiyi kapı-kontrol teorisi ile açıklayan ça-lışmalar vardır. [4][5][6][7] Endorfin, enkefalin, dinorfin gibi endojen opioid salınımı da akupunktur analjesine katkıda bulunabilir. Akupunkturda birçok uygulama tekniği bulunmaktadır.…”
Section: Discussionunclassified
“…These might be associated with balance flow of bodily 'energy' or 'Xi' according to the Chinese-medicine theory after the acupuncture stimulation, which has been verified by neurophysiological interaction. [24][25][26] Finally, it could be argued that the minimal beneficial effects of electroacupuncture, only around 2% reduction during 6 weeks of treatment, can be easily obtained by other management methods such as diet control or drug therapy. However, because of its lack of adverse reactions and the lasting effect on reducing WC, electroacupuncture might be a preferred or synergistic treatment option for obesity control.…”
Section: Discussionmentioning
confidence: 99%